Environmental effects of a vehicle tax reform: Empirical evidence from Norway - Alice Ciccone (University of Oslo, Department of Economics, 2015)
In 2007, the Norwegian government reformed the vehicle registration tax in order to reduce the carbon intensity of the new car fleet by incentivizing the purchase of more fuel efficient cars. This paper identifies the impact of the new tax structure on three main dimensions: (i) the average CO2 emissions intensity of new registered vehicles, (ii) the relative change in sales between low and high polluting cars and (iii) the market share of diesel cars. A Difference in Difference approach is employed to estimate the short run effects on each outcome variable of interest. The results show that the average CO2 intensity of new vehicles was reduced in the year of the implementation of the reform by about 7.5 g of CO2/km. This reduction is the result of a 12 percentage points drop in the share of highly polluting cars and of an increase of about 20 percentage points in the market share of diesel cars.
Keywords: H25; L62; Q51; Q53; Q54; Q58; R48; 330; CO2 emissions intensity; New vehicles; Vehicle registration tax; Tax reform; Norway; Diesel